Examining Audit Culture In The Pesantren Environment: A Discourse Based Study - Ali Djamhuri; Wiwik Hidayah Ekowati; Husnul Hatimah; Ida Ayu Budhananda Munidewi (Fakultas Ekonomi Universitas Negeri Manado, 2024)
Auditing is known as technical, but at least for anthropologists it cultural. What they termed audit culture may be manifested in various activities which have a direct impact on social life such as maintenance of their private space. This article qualitatively examines audit culture in Pesantren located in Malang and Blitar. Interview, observation and documentary data collection were used in this study. Data were analized by getting the benefit of the concept of Foucauldian governmentality and discourse analysis. It is found that, the term audit culture is a rather strange in Pesantren circle. Audit is better known in its formality as examinations of financial reports. Pesantrens agree on the importance of instilling audit values ​​ a form of accountability since it is in accord to the Islamic teachings. Its implementation, however, must contextual to the Pesantren, including in relation to the availability of supporting human resources and the required technology.